KAJIAN KEMAMPUAN DRAINASE DALAM MENAMPUNG INTENSITAS HUJAN MAKSIMUM PADA KAWASAN PERUMAHAN DI KELURAHAN DUMAI KOTA - Rasoel Hamidy; Mubarak Mubarak; Reni Okta Vironika (Program Pascasarjana Universitas Riau, 2011)
The purpose of this study is to analyze the maximum precipitation intensity changes between theperiod 2002 - 2009 and know the drainage capacity to accommodate the maximum rainfallintensity. This research was conducted in the Village District Town Dumai, Dumai City who isprone to occurrence of inundation / flooding during rain. The research method using descriptiveof an explorative approach that aims to describe the condition and status of the phenomenon ofthe drainage channel and residential environment. The results showed that rainfall intensity forrainfall duration 30 minutes with 10-year anniversary when obtained at 257.999 mm / hour. Thecalculation of drainage channels that can accommodate a maximum flow rate / peak dischargecontained in SP1 primary drainage and secondary drainage channels SS1, SS4, and SS11. Theinability of other drainse channel accommodate the maximum flow causing inundation /flooding, in addition to blockage of drainage channels by the waste also adds to the severity ofthe situation